(untitled) (Fiep Bulletin - online, 2015)
The subclinical hypothyroidism is characterized by the increased serum value of thyrotropin (TSH), normal concentrations of triiodothyronine free (FT3) and serum free thyroxine (FT4). The aim of the present study was to compare the level of physical condition of seven patients with seven healthy women, by the ergoespirometry. The data had been compared through the test of Mann-Whitney U (p<0.05). The body fat was not different between the groups (p=0.62). The maximal systolic arterial pressure (SAP) was higher in the control group (167.86 ±19.97 mmHg; 141.43 ± 21.16 mmHg; p=0.04) just to the third minute of recovery. The patients’ diastolic arterial pressure (DAP) in rest condition presented a trend of being higher and the difference between the DAP in the third and in the first minute of recovery was higher for the control group (7.5 ±4.18mmHg; 1.67 +2.58 mmHg; p=0.04). The diastolic dysfunction that comet this patients already is known by literature. The heart hate in the rest and exercise peak was not modified in the patients, results that corroborate with Monzani et al (2001). The load, the total duration of the test and the relative oxygen uptake in the exercise peak (ml.kg-1.min-1) had tended to be bigger in the control group, but only 14.19% of the patients reached the anaerobic threshold, while 57.14% of the control group reached it. The subclinical hypothyroidism seems to influence some cardio respiratory variable in rest and during the exercise. The most sensible variables were the arterial pressure, the peak oxygen uptake, the duration of the test, the maximal load and the characterization of the anaerobic threshold.